ENTREPRENEURIAL INTENTION DI KALANGAN MAHASISWA DI SURABAYA DALAM TINJAUAN COGNITIVE FLEXIBILITY DAN RISK-TAKING PROPENSITY - Benedictus Felex Giarto; Yonathan Palumian; Wilma Laura Sahetapy (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
Entrepreneurship is a skill that needs to be possessed by the younger generation and should be nurtured from an early age. This study aims to explain the impact of risk-taking propensity and cognitive flexibility on entrepreneurial intention in final year students in Surabaya. The research method used is quantitative research. The study population consisted of final year students in the city of Surabaya, with a sample size of 130 respondents. The variables studied include risk-taking propensity, cognitive flexibility, and entrepreneurial intention. Data was collected using a questionnaire. Data processing methods include validity and reliability tests, as well as classical regression assumptions and multiple linear regression. The research findings show that risk-taking propensity and cognitive flexibility have a positive and significant influence on entrepreneurial intention. Entrepreneurship is a skill that needs to be possessed by the younger generation and should be nurtured from an early age. This study aims to explain the impact of risk-taking propensity and cognitive flexibility on entrepreneurial intention in final year students in Surabaya. The research method used is quantitative research. The study population consisted of final year students in the city of Surabaya, with a sample size of 130 respondents. The variables studied include risk-taking propensity, cognitive flexibility, and entrepreneurial intention. Data was collected using a questionnaire. Data processing methods include validity and reliability tests, as well as classical regression assumptions and multiple linear regression. The research findings show that risk-taking propensity and cognitive flexibility have a positive and significant influence on entrepreneurial intention.